2014
DOI: 10.1007/s11266-014-9545-z
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Subjective Well-Being Premium in Voluntary Sector Employment?

Abstract: Previous studies have found that employment in the voluntary sector offers a so-called 'job satisfaction premium': despite lower salaries, voluntary sector employees are more satisfied with their jobs than workers in other sectors. This paper examines whether voluntary sector employees also experience a subjective well-being premium. Using data from the UK Annual Population Survey 2012/2013, we find that voluntary sector employees do have higher levels of subjective well-being but this subjective well-being pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…For other employees (as opposed to those involved through work-integration), there is an acknowledgement of the effect on their own wellbeing of working for what they perceive to be an ethically sound organisation (see Kamerāde and McKay, 2015 ): “Like even working for a business that you care about, it builds your confidence, it improves your wellbeing, that kind of thing. So, there are the very soft outcomes that go with it as well.…”
Section: Resultsmentioning
confidence: 99%
“…For other employees (as opposed to those involved through work-integration), there is an acknowledgement of the effect on their own wellbeing of working for what they perceive to be an ethically sound organisation (see Kamerāde and McKay, 2015 ): “Like even working for a business that you care about, it builds your confidence, it improves your wellbeing, that kind of thing. So, there are the very soft outcomes that go with it as well.…”
Section: Resultsmentioning
confidence: 99%
“…Baines et al (2014) also found that self-care is a further problematic aspect of this new non-profit culture since employees are the ones who need to monitor their own well-being and seek out self-care practices on their own. Kamerāde and McKay (2014) also note that pressures of working at non-profit organizations extends beyond the workplace, meaning that employees who need to be selfreliant to prevent burnout will potentially be affected in their personal lives.…”
Section: Collective Vs Individualmentioning
confidence: 99%
“…While women are the ones doing unpaid overtime, men in the non-profit sector often do not experience burnout in the same way that women do, nor do they report using any specific self-care practices to combat that burnout (Baines et al, 2014). In Kamerāde and McKay's study, they found that while both male and female non-profit sector employees did feel a higher level of fulfillment from working in that sector, women reported lower life satisfaction than men as a result of their non-profit employee status (Kamerāde & McKay, 2014). The scholarship on women in nonprofit organizations has largely focused on the unique number of women in leadership roles at non-profits (English & Peters, 2011).…”
Section: Non-profit Sector Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations